2023
DOI: 10.4236/fns.2023.142008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Hydrocolloids on Suspension Stability of Chia Seeds (<i>Salvia hispanica</i> L.) in Mango Beverage and Mango Flavored Beverage

Abstract: With the developing of juices and beverages industry, the processors need to bring new nutritional fortified products to capture the market as per the demand of the consumer who needs healthier product. Thus, this study aimed to the production of mango beverage and mango flavored beverage fortified with chia seeds; evaluate the chemical properties of chia seeds and study the effect of adding carboxymethyl cellulose, xanthan gum and low acyl gellan gum at the concentrations of 0.05% and 0.1% on the stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
4
1
0
Order By: Relevance
“…Results of the current study were also compared with the color values provided by another study of Buse et al [45], which showed similar fndings, witnessing the signifcant efect of diferent microwave heat durations on the colors of the treated beverages. A slight decrease in the L * value in all treatments of chia seeds added to mango beverage was also reported by Aamer et al [33], and these results agreed with the present ones.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Results of the current study were also compared with the color values provided by another study of Buse et al [45], which showed similar fndings, witnessing the signifcant efect of diferent microwave heat durations on the colors of the treated beverages. A slight decrease in the L * value in all treatments of chia seeds added to mango beverage was also reported by Aamer et al [33], and these results agreed with the present ones.…”
Section: Resultssupporting
confidence: 94%
“…Visible changes in the color of whey beverage added with chia seeds were signifcantly dependent upon microwave heat treatment durations and storage days. For the values of b * , all treatments had higher values than the control; however, a change in the time of microwave treatment had a signifcant efect on a * and b * values in all studied samples, and these results are in agreement with those of Aamer et al [33].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations